Graphene Photodetectors: Large‐Scale Production of Bismuth Chalcogenide and Graphene Heterostructure and Its Application for Flexible Broadband Photodetector (Adv. Electron. Mater. 5/2016). (May 2016) - Song, Jingchao; Yuan, Jian; Xia, Fang; Liu, Jingying; Zhang, Yupeng; Zhong, Yu Lin; Zheng, Jialu; Liu, Yan; Li, Shaojuan; Zhao, Meng; Tian, Zhiming; Caruso, Rachel A.; et al.
Abstract : In article number 1600077, Bao et al. demonstrate large‐scale production of Bi2 Sex Te3‐x –graphene van deer Waals heterostructures using a solvothermal method. Free‐standing films produced from this heterostructure show improved electrical, photoelectric and mechanical properties, making their photoresponsive material promising for flexible photodetectors that can operate from visible to near‐infrared wavelengths.